Faktor-Faktor Keberhasilan Program Promosi Kesehatan “Gempur Stunting” Dalam Penanganan Stunting di Puskesmas Rancakalong Sumedang - Tatang Manggala; Jenny Ratna Suminar; Hanny Hafiar (Fakultas Ilmu Komunikasi Universitas Pancasila, 2021)
The Indonesian government has set 60 priority districts/cities for stunting handling. Based on this determination, Sumedang is included in the priority district because in 2018 the stunting prevalence rate reached 32%. The selection conducted by Bappeda Sumedang contained 10 villages where the prevalence rate of stunting was high and three of them were villages in Rancakalong. To overcome this, the Rancakalong Community Health Center initiated the “Gempur Stunting” Health promotion Program which has succeeded in reducing the prevalence of stunting from 27.7% to 19.8%, making it an exemplary health promotion program. This research was conducted to determine the success factors of the